Impact of TB Epidemic on Worker and Firm Productivity: Regional Perspective from Ukraine - Olena Nizalova; Oleksandr Shepotylo (Global Labor Organization (GLO), 2023)
This paper investigates the indirect economic impact of tuberculosis epidemic in one of the high-burden countries, focusing on the productivity at the individual level measured by the average wages and at firm level measured by the average total factor productivity (TFP). We use unique administrative data collected at the level of firms and regions for 2003-2009 and find that the ongoing tuberculosis (TB) epidemic has considerable indirect economic costs in terms of lost productivity and related inefficien- cies. First of all, both firms and individuals in regions with higher TB prevalence have significantly lower TFP and wages. Moreover, consistent with the Compensating Wage Differentials theory and after controlling for the TB prevalence, the risk of contracting the disease - TB incidence rate - is associated with higher wages and higher produc- tivity - a kind of premium for individuals and firms to operate in a risky environment. The latter can also be viewed as a source of inefficiency as this may prevent firms from entering more competitive markets. Additional analysis reveals strong spatial effects which are consistent with the infectious nature of the diseases and emphasize the im- portance of containing the epidemic. Overall, we estimate that a 10% decrease in the TB prevalence can lead to a 1.05% gain in GDP: 0.15% in terms of higher individual productivity and 0.89% in terms of firms' productivity.
Keywords: O18; I15; J24; 330; Tuberculosis; Productivity; Regional Wage; Total Factor Productivity; TB Epidemic